NIODA and the Problem of Evil: God as Ultimate Determiner - Sánchez Cañizares, Javier (Religions, 2023)
The problem of evil permeates contemporary theodicy, raising the question of how an omnipotent and benevolent God can allow its existence. Exploring this inquiry is inherently tied to investigating divine action, specifically the interplay between time and eternity within a temporary creation. In recent decades, the Non-Interventionist Objective Divine Action (NIODA) project has endeavored to present a science-backed perspective that acknowledges a respectful divine action harmonizing with the workings of nature. However, this viewpoint has faced criticism from various angles, particularly for its perceived inability to provide a definitive response to the problem of evil. This contribution aims to overcome these criticisms. While not necessarily endorsing the NIODA proposal, it seeks to present a fresh outlook on the question of evil that aligns with NIODA, addressing the dichotomy between the unity and plurality of divine action in the world and offering novel insights for the Christian doctrine of creation.